A novel framework on exact average symbol error probabilities of multihop transmission over amplify-and-forward relay fading channels - Yilmaz, Ferkan; Kucur, Oğuz; Alouini, Mohamed Slim (My University, 2010)
In this paper, we propose an analytical framework on the exact computation of the average symbol error probabilities (ASEP) of multihop transmission over generalized fading channels when an arbitrary number of amplify-and-forward relays is used. Our approach relies on moment generating function (MGF) framework to obtain exact single integral expressions which can be easily computed by Gauss-Chebyshev Quadrature (GCQ) rule. As such, the derived results are a convenient tool to analyze the ASEP performance of multihop transmission over amplify-and-forward relay fading channels. Numerical and simulation results, performed to verify the correctness of the proposed formulation, are in perfect agreement. © 2010 IEEE. © 2011 Elsevier B.V., All rights reserved.
2010 7th International Symposium on Wireless Communication Systems, ISWCS'10 -- York -- 82865
Keywords: Amplify-and-forward relay technology; Average symbol error probabilities; Meijer's G and Fox's H functions; Multihop transmission